A vapoluminescent Eu-based metallo-supramolecular polymer - Sato, Takashi; Higuchi, Masayoshi (Chemical communications (Cambridge, England), 2012)
An Eu-based metallo-supramolecular polymer (polyEu) was prepared by self-assembly coordination polymerization. Unique vapoluminescence property of polyEu triggered by acid-base vapor was found and a photoluminescence display in switchable imaging by acid-base vapor was fabricated.